2013
DOI: 10.1152/advan.00119.2012
|View full text |Cite
|
Sign up to set email alerts
|

Do learning approaches of medical students affect their satisfaction with problem-based learning?

Abstract: The aim of this research was to determine the satisfaction of medical students with problem-based learning (PBL) and their approaches to learning to investigate the effect of learning approaches on their levels of satisfaction. The study group was composed of medical students from three different universities, which apply PBL at different levels in their curricula. The revised two-factor study process survey was applied to the study group to determine their approaches to learning as "deep" or "surface" learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 13 publications
2
37
0
13
Order By: Relevance
“…According to Groves (2005), students develop a deep approach to learning to learn and improve individuals learn their self-efficacy during problem-based learning (PBL). This finding is similar to previous studies that reported that students tend to adopt a deep approach to learning rather than surface approach to learning (Groves, 2005;Dolmans, Wolfhagen, & Ginns, 2010;Gurpinar et al, 2013). Students with higher scores in deep approach to learning have higher internal motivation and intention to use deep approach to learning (Sabzevari, Abbaszade & Borhani 2013).…”
Section: Tabel 4 Frequency Distribution Of Respondents Based On Theirsupporting
confidence: 90%
“…According to Groves (2005), students develop a deep approach to learning to learn and improve individuals learn their self-efficacy during problem-based learning (PBL). This finding is similar to previous studies that reported that students tend to adopt a deep approach to learning rather than surface approach to learning (Groves, 2005;Dolmans, Wolfhagen, & Ginns, 2010;Gurpinar et al, 2013). Students with higher scores in deep approach to learning have higher internal motivation and intention to use deep approach to learning (Sabzevari, Abbaszade & Borhani 2013).…”
Section: Tabel 4 Frequency Distribution Of Respondents Based On Theirsupporting
confidence: 90%
“…9 By way of example of evaluating teaching and assessment changes, Bevan et al 10 demonstrated that traditional lectures/examinations encouraged surface learning, whilst student-centered workshops/multiple examinations throughout a biochemistry subject encouraged deep learning. With regard to the health professions, there are numerous examples 3,[11][12][13][14][15][16] where the SPQ and it's more recent incarnation, the revised 2 factor version of the SPQ (R-SPQ-2F), 9 have been used. Interested readers are encouraged to explore the summary of learning approaches in Data were entered into Microsoft Excel.…”
Section: Introductionmentioning
confidence: 99%
“…Higher medical colleges and universities should shoulder the important responsibility of medical staff to continue education. We think, should be in the developing of higher medical education at the same time, increase the medical workers, professional training and continuing education, unceasingly promote the medical workers with the domestic and international cooperation, exchange and competition among, the continuing education, academic exchange and cooperation has become a common, often way of learning [12].…”
Section: Modernization and International Standardizationmentioning
confidence: 99%